2019
DOI: 10.1007/s11605-018-3910-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Feasibility of Large Gastrotomy Closure Using a Flexible Tissue Glue Based on N-Butyl-2-Cyanoacrylate: Experimental Study in Pigs

Abstract: Our results suggest that flexible cyanoacrylates could be a feasible alternative to improve the clinical outcome of the closure of hollow viscera through more efficient sutureless procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Those studies showed that cyanoacrylate remained in the tissue for an extended period and that its efficacy persisted. 8 -11 Espin Alvarez et al described cyanoacrylate as more durable than synthetic sutures in gastrostomy closures in their experimental porcine study 8. Those authors also reported that the histopathological and inflammatory variables were similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies showed that cyanoacrylate remained in the tissue for an extended period and that its efficacy persisted. 8 -11 Espin Alvarez et al described cyanoacrylate as more durable than synthetic sutures in gastrostomy closures in their experimental porcine study 8. Those authors also reported that the histopathological and inflammatory variables were similar in both groups.…”
Section: Discussionmentioning
confidence: 99%